Phasing out payroll tax subsidies - Anna Herget; Regina T. Riphahn (International Tax and Public Finance, 2025)
Many countries subsidize low-income employments or small jobs. These subsidies and their phasing out can generate labor market frictions and distort incentives. The German Minijob program subsidizes low-income jobs. It generates a 'Minijob trap' with substantial bunching along the earnings distribution. Since 2003, the newly introduced Midijob subsidy aims to reduce the Minijob-induced notch in the net earnings distribution. Midijobs reduce payroll taxes for employments above the Minijob earnings ceiling. We investigate whether introducing Midijobs reduced the Minijob trap. We apply a regression discontinuity design using administrative data and a difference-in-differences estimation using survey data. While in both cases our results show a small positive overall effect of Midijobs on transitions out of Minijobs, they are effective only for a narrow treatment group.
Keywords: J21; J38; H24; 340; Midijobs; Minijobs; Payroll tax subsidy; Causal effects; Difference-in-differences; Regression discontinuity; SOEP; SIAB